Improving Public Participation for Land Use Planning in Malaysia: Can Participatory GIS help?u (Journal of Governance and Development (JGD), 2018)
Technology advancement in the form of Participatory GIS (PGIS) has emerged as a method for gathering public knowledge and opinions to enhance public participation development planning. There is also a huge potential for PGIS to be applied in developing countries because of its capability to pull the public toward a more active role both in participation and the decision-making process. Researchers have used various types of geo-information technology to encourage public participation, but their studies showed that public interest in participating in any kind of planning activities has not increased, thus failing to attract the public attention to participate. The article focuses on the description of the potential beneï¬ts and barriers of PGIS implementation for land use planning in Malaysia.